Assessing the Livelihood Transformation through NABARD-Sponsored Farmer Producer Unions in Chhattisgarh's Agriculture - Manharan Anant, Gaurav Sahu, Sushma Tiwari, (European Economic Letters (EEL), 2024)
Agriculture holds a paramount position in the development of nations, and in the context of a developing state like Chhattisgarh, its significance is no less profound. As of 2019-2020, agriculture contributes substantially to the state's GDP, shaping its economic landscape. Approximately 60% of Chhattisgarh's total population, which stands at [current population], is directly or indirectly associated with agriculture, underlining its pivotal role in livelihood sustenance. Chhattisgarh's agricultural sector serves not only as a source of livelihood but also as a fundamental pillar of the state's economy. The success of various schemes, market stability, and even political equilibrium in Chhattisgarh are intricately linked to the well-being of its agricultural sector. The state's industries, foreign exchange earnings, and overall prosperity are contingent on the growth and prosperity of agriculture. In this landscape, the role of Farmer Producer Organizations (FPOs) has emerged as a catalyst for enhancing the livelihoods of farmers in Chhattisgarh. Drawing inspiration from successful models like the Amul Dairy Production Organization, FPOs are playing a crucial role in the state's agricultural development. As per the available data, Chhattisgarh has experienced a growth in its population from 2011 census data 2.55 Crores to an estimated current population 3.15 Crore. A significant portion, approximately 80 % of the state's population, relies directly or indirectly on agriculture for their livelihoods. Despite the state's demographic size, agricultural holdings in Chhattisgarh are predominantly small, highlighting the importance of sustainable agricultural practices and supportive initiatives for the well-being of farmers. In essence, agriculture stands as the primary source of income and livelihood for Chhattisgarh, and the state's overall progress is intricately connected with the growth and prosperity of its agricultural sector. Initiatives like FPOs play a crucial role in fostering sustainable development and improving the lives of farmers in Chhattisgarh.